The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1007/s11102-012-0436-2
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase cytochrome P450 enzyme expression in prolactinomas and its relationship to tumor behavior

Abstract: The aim of the study was to evaluate the presence of aromatase cytochrome P450 enzyme (P450AROM) expression in normal pituitary tissues and tumor tissues of patients with prolactinoma and to examine the impact of the P450AROM expression on clinical outcome. Twenty-six consecutive human pituitary tissue samples were obtained from autopsies performed at the Institute of Forensic Medicine. Sixty-four patients who had an adenomectomy between 2000 and 2009 after prolactinoma diagnosis with histologically confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 30 publications
5
18
0
Order By: Relevance
“…Similarly, in the study of Akıncı et al, ER-beta expression was seen higher in controls and invasive adenomas than noninvasive adenomas, although the difference was not statistically significant [4]. In addition, the relationship between aromatase and ER-beta expression was negatively directed but not statistically significant [4]. We observed a significant negative correlation between aromatase and ERalpha expression.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Similarly, in the study of Akıncı et al, ER-beta expression was seen higher in controls and invasive adenomas than noninvasive adenomas, although the difference was not statistically significant [4]. In addition, the relationship between aromatase and ER-beta expression was negatively directed but not statistically significant [4]. We observed a significant negative correlation between aromatase and ERalpha expression.…”
Section: Discussionsupporting
confidence: 80%
“…In contrast to aromatase expression, ERalpha expression was lower in the acromegaly group than in normal pituitary tissue. The role of local aromatization in prolactinoma has recently been shown by Akıncı et al In his study, aromatase expression was found to be higher in prolactinomas than in normal pituitary tissue, particularly in males with invasive adenoma, but no significant relationships were detected among p53, Ki-67, remission status, and aromatase expression [4]. Moreover, aromatase expression has also been observed in females with prolactinomas [26].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Moreover, we reported a very strong correlation between the pituitary expression of aromatase and the incidence of spontaneous prolactinomas in old rats [3] and humans [4]. Similar results were later reported by different authors in non-tumoral pituitaries of humans and different animal species [5][11] and in human prolactinomas [12]. However, the physiological relevance of aromatase and the possible aromatization of testosterone to estradiol in the regulation of pituitary hormones are not well known.…”
Section: Introductionsupporting
confidence: 85%